Dynamic Change in Oral Microbiota of Children With Cleft Lip and Palate After Alveolar Bone Grafting. (November 2022) - Zhang, Kejia; Zhou, Xuan; Qin, Jinwei; Zhang, Weibing; Pan, Yongchu; Wang, Hua; Lin, Jiuxiang; Liu, Luwei; Jia, Yilin
Objective : To investigate the longitudinal influence of alveolar bone grafting on the oral microbiota of children with cleft lip and palate (CLP). Materials and methods : Twenty-eight children with nonsyndromic CLP were recruited and underwent secondary alveolar bone grafting at the first time. Unstimulated saliva and plaque samples were collected from the subjects preoperatively and at 2 days, 1 month, and 3 months postoperatively. The v3–v4 hypervariable regions of the 16S rRNA gene from bacterial DNA were sequenced using the Illumina MiSeq sequencing platform. Results : The alpha diversity of the saliva and plaque microbiota was significantly decreased at 2 days postoperatively and then increased at 1 and 3 months postoperatively. The saliva and plaque microbiota compositions at 2 days postoperatively differed from those at the other time points, and the microbiota compositions at 1 and 3 months postoperatively showed a gradual shift toward the preoperative composition. The saliva, but not plaque, microbiota composition 3 months postoperatively was similar to that preoperatively. Conclusion : The effect of secondary alveolar bone grafting on the plaque microbiota in children with CLP lasted longer than the saliva microbiota. Alveolar bone grafting altered the saliva microbiota in children with CLP within 3 months postoperatively.